Fluorescence studies on new potential antitumoral 1,3-diarylurea derivatives of thieno[3,2-b]pyridines in solution and in nanoliposomes - Castanheira, Elisabete M. S. (2011)
This work was supported by Fundação para a Ciência e a Tecnologia (Portugal), QREN and FEDER through CFUM, CQ/UM and Project PTDC/QUI/81238/2006 cofinanced by FCT and program FEDER/COMPETE (FCOMP-01-0124-FEDER-007467).